AN IMPROVEMENT OF PIEZOELECTRIC POWER PLANT DESIGN IN SLEEP POLICE BLUFF BODY BASED ON CANTILEVER SYSTEM - Johannes Stevanus Parulian Simanjuntak; Solly Aryza; Adi Sastra P Tarigan (Sean Institute, 2022)
Indonesia's electricity demand is predicted to increase every year, this can cause Indonesia to become an energy importer in the coming year. These problems can be overcome by developing alternative energy, one of which is by utilizing waste vibration energy or pressure energy from the movement of motorized vehicles, cars and pedestrians and even wind gusts in the use of piezoelectric speed bumps. Piezoelectricity is an energy harvester. Piezoelectric with cantilever mechanism produces vibration and deflection repeatedly, causing an electric voltage. The piezoelectric speed bump designed in this study consists of a speed bump system that serves to receive input from motorized vehicle pressure, piezoelectric cantilever system as a component producing electrical energy and energy harvesting system as energy harvester from piezoelectric materials. One system module consists of a parallel piezoelectric circuit connected to the MB39C811 buck converter. This paper will discuss the mechanism of design analysis and modeling of a piezoelectric power generation system on a body bluff-based speed bump with a cantilever system for variations in motor vehicle speed by means of physical modeling. In the piezoelectric bump bluff body, it can be seen that the air flow when passing through the triangular cross section increases in speed so that the resulting vortex has a high speed. This is what causes high vibrations in the piezoelectric so that the maximum voltage and the average voltage have the highest values. The piezoelectric speed bump is capable of generating electric power with an input of 60 times that of a motor vehicle above 2.166mWh with an efficiency of 2.